2020
DOI: 10.3390/mi11070652
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Surface Waviness Error of Fresnel Micro-Structured Mold by Using Non-Integer Rotation Speed Ratio in Parallel Grinding Process

Abstract: Fresnel micro-structured lenses are widely used in the field of modern optoelectronic technology. High-precision Fresnel micro-structured mold is the key technology to achieve its large-scale replication production. Focusing on the surface waviness error of Fresnel micro-structured mold machined by parallel grinding process, this paper conducted theoretical modeling and experiment research. Based on the grinding kinematics theory, the simulation models of the surface waviness topography and the circular wavine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In addition, the grinding marks could be weakened and the surface finish would be improved when grinding with the middle phase shift in parallel grinding process. Pan et al 15,16 indicated that the Sa and Sq value reached the maximum when the wave-shift was equaled to 0, which were 118 and 142 nm respectively, and the Sa and Sq value reached the minimum when the wave-shift was equaled to 1/4 in parallel grinding, which were 16 and 20 nm respectively. In addition, the surface waviness could be reduced when grinding with a non-integer rotation-speed-ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the grinding marks could be weakened and the surface finish would be improved when grinding with the middle phase shift in parallel grinding process. Pan et al 15,16 indicated that the Sa and Sq value reached the maximum when the wave-shift was equaled to 0, which were 118 and 142 nm respectively, and the Sa and Sq value reached the minimum when the wave-shift was equaled to 1/4 in parallel grinding, which were 16 and 20 nm respectively. In addition, the surface waviness could be reduced when grinding with a non-integer rotation-speed-ratio.…”
Section: Introductionmentioning
confidence: 99%